Hypertensive Crisis Management Strategies, and Outcome in the Hyperacute Phase of Acute Hemorrhagic Stroke - Mayurapak, Chidchanok; Intawong, Manatsaporn; Phonphet, Chennet; Suwanno, Jom (Health Science Journal of Thailand, 2021)
We examined hypertensive crisis management strategies and outcome in the first 6-hour after hospitalization with acute hemorrhage stroke (AHS). A descriptive, cross-sectional study was performed. We recruited 53 patients from one tertiary care hospital, during January to December, 2018. All data were collected from medical record file, and nursing note using three forms include patients characteristic, management strategies and outcome. Descriptive and Fischer’s exact test was performed for data analysis by using statistical program. A total of 49 (92.5%) of the patients had hypertensive crisis, 83.7% received hypertensive lowering medication, and all (100%) of whom was prescribed calcium channel blockers drug class. Approximately, two-third (59.2%) of the patient with hypertension crisis had reach mild-target blood pressure control. However, management outcome among medication and none medication groups was insignificant. Our clinical point is to call a statement of practice protocol for patient care team approach to improve clinical outcome and patient safety.